2000
DOI: 10.1007/s005310000127
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater chlorophycean algae in recent marine sediments of the Beaufort, Laptev and Kara Seas (Arctic Ocean) as indicators of river runoff

Abstract: Freshwater chlorophycean algae in recent marine sediments of the Beaufort, Laptev and Kara Seas (Arctic Ocean) as indicators of river runoff Abstract Freshwater chlorophycean algae are characteristic organic-walled microfossils in recent coastal and shelf sediments from the Beaufort, Laptev and Kara seas (Arctic Ocean). The persistent occurrence of the chlorophycean algae Pediastrum spp. and Botryococcus cf. braunii in marine palynomorph assemblages is related to the discharge of freshwater and suspended matte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 42 publications
1
56
1
1
Order By: Relevance
“…Chl b occurs mainly in green algae and terrestrial plants (Kowalewska 2005) and is less stable than chl a (Kowalewska & Szymczak-Zyla 2001); however, degradation products of chlorophylls are usually very persistent in sediment records (Scheer 1991). Freshwater green algae have been used as a marker of river runoff in the Beaufort, Laptev, and Kara Seas (Matthiessen et al 2000), and high sedimentary chl b contents have been attributed to the intensive influence of riverine fresh water (Kowalewska et al 1996, Matthiessen et al 2000. In the fall, the high levels of chl b degradation products and the strong negative correlation of chl b degradation products with distance from the river suggest that, as for the POM, the influence of degraded material from the Mackenzie River is high, especially on the shelf; however, this material probably represents a small portion of the total organic matter present in the sediment, and this signal is lost when studying stable isotopes in the bulk sediment.…”
Section: River Influencementioning
confidence: 99%
“…Chl b occurs mainly in green algae and terrestrial plants (Kowalewska 2005) and is less stable than chl a (Kowalewska & Szymczak-Zyla 2001); however, degradation products of chlorophylls are usually very persistent in sediment records (Scheer 1991). Freshwater green algae have been used as a marker of river runoff in the Beaufort, Laptev, and Kara Seas (Matthiessen et al 2000), and high sedimentary chl b contents have been attributed to the intensive influence of riverine fresh water (Kowalewska et al 1996, Matthiessen et al 2000. In the fall, the high levels of chl b degradation products and the strong negative correlation of chl b degradation products with distance from the river suggest that, as for the POM, the influence of degraded material from the Mackenzie River is high, especially on the shelf; however, this material probably represents a small portion of the total organic matter present in the sediment, and this signal is lost when studying stable isotopes in the bulk sediment.…”
Section: River Influencementioning
confidence: 99%
“…ZEISS) using  400 and  1000 magnification. For further details we refer to Matthiessen et al (2000).…”
Section: Palynomorphsmentioning
confidence: 99%
“…Field observations showed that collapsing tundra hummocks are transported along with the thaw stream and are deposited directly on the shore, where they are leached by seawater and broken down by wave action, their remains partially buried in marine sediments. Fresh water algae becomes present at 800 to 2000 m distance from the RTS and in the lower part (N6 cm depth) of the short core, probably due to a mix of autochtonous production within the brackish water column and the influx of allochtonous terrestrial sources from the coast, rivers, or sea ice (Matthiessen et al, 2000;Poulin et al, 2014). The influence of the Mackenzie River inflow in the eastern part of the Yukon coast is particularly strong and is probably an additional source of terrestrial OM at the study site (Carmack and Macdonald, 2002).…”
mentioning
confidence: 99%